The Transformation of Hindu Dharma Values into Legal Norms: Ambiguity in the Awig-Awig of Kesian Customary Village - Wacika, Made Wiswani; Ardini, Ni Putu Ayu Meylan; Dewi, Anak Agung Istri Ari Atu (SASI, 2026)
Introduction: Customary Village in Bali regulates the social and religious life of its community through customary law known as Awig-Awig. In Kesian Customary Village, Awig-Awig reflects the transformation of Hindu Dharma values into written normative rules intended to preserve social harmony and communal order. However, several provisions remain general and abstract, creating vage normen (vague norms) that generate normative ambiguity and potentially weaken legal certainty and the protection of the rights of krama Village, particularly in matters related to customary sanctions and inheritance.Purposes of the Research: This research aims to analyze the formulation of Hindu Dharma values within the Awig-Awig of Kesian Customary Village and to examine the juridical implications of these vague norms on the consistency of customary law enforcement and the protection of village community rights.Methods of the Research: This study employs normative legal research focusing on the ambiguity of Hindu Dharma values in written customary law. It applies statutory, conceptual, and philosophical approaches using primary legal materials such as the Awig-Awig of Kesian Customary Village and secondary materials including Hindu legal literature and customary law doctrines, which are analyzed through qualitative normative interpretation.Results of the Research: The findings show that Article 26 paragraph (3) and Article 49 contain vague norms due to the absence of clearly defined prohibited acts, determination procedures, and measurable sanctions. This ambiguity gives broad discretionary authority to customary leaders and risks inconsistent enforcement. The novelty of this research lies in providing a normative critique of Awig-Awig formulation from the perspective of legal certainty and recommending clearer legal standards to strengthen the protection of village community rights.